Law versus economics? How should insurance intermediaries influence the insurance demand decision - Annika Pape (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
How should intermediaries influence the insurance demand decision? The answer must refer to the interdependence of economic determinants and legal duties. Intermediaries potentially guide demand decisions by delivering objective information and by considering individuals' situation and economic circumstances. The economic theory provides determinants that are essential for the insurance demand decision. Undoubtedly, consumers lack information about certain variables, and therefore misjudge their demand for insurances. In response to the consumer, an intermediaries' task is to discover possible misjudgments and to provide the correct information. Since the information in the insurance market is asymmetrically distributed, an insurance agent has an incentive to behave opportunistically, a tendency that is reinforced by the remuneration scheme in Germany. In 2007/2008, insurance intermediaries became regulated by law. That law states, among other things, the four basic obligations of insurance intermediaries and a liability rule to sanction violations. In order to interpret and substantiate the legal terms, those have to match the relevant economic determinants to state the ideal behavior of an intermediary.
Keywords: G22; D83; D89; K29; K40; 330; insurance; insurance intermediation; advice; liability; Insurance Contract Act